Interface Engineering to Boost Thermal Safety of Microsized Silicon Anodes in Lithium‐Ion Batteries. Issue 7 (1st June 2022) - Liu, Qing; Meng, Tao; Yu, Le; Guo, Songtao; Hu, Yunhuan; Liu, Zhifang; Hu, Xianluo
Abstract: Battery safety is vital to the application of lithium‐ion batteries (LIBs), especially for high energy density cells applied in electric vehicles. As an anode material with high theoretical capacity and natural abundance, Si has received extensive attention for LIBs. However, it suffers from severe electrode pulverization during cycling due to large volume changes and an unstable solid electrolyte interphase (SEI), resulting in accelerated capacity fading and even safety hazards. Therefore, safe and long‐term cycling of Si‐based anodes, especially under high‐temperature cycling, is highly challenging for state‐of‐the‐art high‐energy LIBs. The thermal behavior of SEI is crucial for a high safety battery as the decomposition of SEI is the first step in thermal runaway. Here, highly reversible and thermotolerant microsized Si anodes for safe LIBs are demonstrated. Comprehensive electrochemical/mechanical/thermochemical behaviors of the SEI are systematically investigated. The rational design of robust SEI endows the Si‐based cells with long‐term durability at elevated temperatures and superior thermal safety. This work paves the way for designing industrial‐scale, low‐cost, microsized Si anodes with applications in next‐generation LIBs with high energy densities and high safety. Abstract : Interface engineering of microsized silicon anodes is demonstrated for high thermal safety of lithium ion batteries (LIBs) at high temperatures. An ionic‐liquid‐based electrolyte is compatible with low‐grade microsized Si anodes in the LIBs, which facilitates the formation of a robust solid electrolyte interface (SEI) with thermally stable, high‐modulus, and inorganic‐rich features. The constructed SEI can delay the thermal runaway by inhibiting the SEI decomposition.